Investigation Study of Semi-Bio Briquettes and Synthesis Briquettes From Used Polymer Waste Plastic Bottles - Harmi Tjahjanti, Prantasi; Bamban Jakaria, Ribangun; Febriyan Ikhsanudin, Achmad; Fernanda, Rexy Eca; Akbar, Ali; Fahruddin, A'rasy (Ann Publisher, 2025)
Up to 2022, Indonesians will produce 69 million tons of waste, of which 12.5 million tons, or 18.2%, will be plastic waste. Since 1995, the number has been growing dramatically. Recycling shredded waste to reduce its volume and enable processing into other materials is one way to manage plastic waste appropriately. This study specifically converted plastic bottle waste into briquettes for used polymer waste. Briquettes are made from recycled plastic bottles used to make polymer waste. There are two types of briquettes made from this waste: Semi-Bio Briquettes, which are made from recycled plastic bottles that have been used to make polymer waste mixed with natural materials like wood sawdust and coconut fiber and adhered with starch, and Synthesis Briquettes, which are made from recycled plastic bottles that have been used to make patchwork or fabric waste and paper waste. The next tests include (1) the Calorific Value Test (Bomb Calorimeter Method), (2) the Proximate Test following SNI 01-6235-2000, which assesses bound carbon, moisture content, ash content, volatile matter content, and other factors, and (3) the Gas/Smoke Emission Test following 2017 RI Minister of Environment and Forestry Regulation Standards. SEM was used to examine the microstructure of synthetic and semi-bio briquettes. While the calorific values for synthetic briquettes did not satisfy the specifications, the results for semi-bio briquettes met the standards. The proximate test results, however, revealed that the two briquettes did not meet the specifications for bound carbon content while meeting the standards for volatile matter content and moisture level. However, only semi-bio briquettes meet the requirements for ash content. The CO, CO2, and HC gas/smoke emission tests all yielded data that complied with the 2017 RI Minister of Environment and Forestry Regulation requirements. Semi-bio briquettes' microstructure observations were less hollow and denser than those of synthetic briquettes.